2019
DOI: 10.1038/s41598-019-56163-x
|View full text |Cite
|
Sign up to set email alerts
|

Cleaved CD31 as a target for in vivo molecular imaging of inflammation

Abstract: There is a need for new targets to specifically localize inflammatory foci, usable in a wide range of organs. Here, we hypothesized that the cleaved molecular form of CD31 is a suitable target for molecular imaging of inflammation. We evaluated a bioconjugate of D-P8RI, a synthetic peptide that binds all cells with cleaved CD31, in an experimental rat model of sterile acute inflammation. Male Wistar rats were injected with turpentine oil into the gastrocnemius muscle two days before 99mTc-HYNIC-D-P8RI (or its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…In our previous studies, we demonstrated that P8RI, a CD31 agonist peptide, effectively rescued and sustained the functionality of CD31 ITIM in T lymphocytes ( Clement et al, 2015 ; Fornasa et al, 2012 ; Fornasa et al, 2010 ) and macrophages ( Andreata et al, 2018 ), thereby providing promising potential for theranostic applications ( Hoang et al, 2018 ; Vigne et al, 2019 ). In the context of neutrophils, we found that the CD31 agonist consistently sustained CD31 phosphorylation ( Figure 4—figure supplement 1A ) and clustering ( Figure 4—figure supplement 1B ) during fMLP activation ( Figure 4—figure supplement 1C ), specifically targeting the CD31 molecule ( Figure 4—figure supplement 1D ), and fine-tuning cytoskeleton dynamics ( Figure 4—figure supplement 1E ).…”
Section: Resultsmentioning
confidence: 99%
“…In our previous studies, we demonstrated that P8RI, a CD31 agonist peptide, effectively rescued and sustained the functionality of CD31 ITIM in T lymphocytes ( Clement et al, 2015 ; Fornasa et al, 2012 ; Fornasa et al, 2010 ) and macrophages ( Andreata et al, 2018 ), thereby providing promising potential for theranostic applications ( Hoang et al, 2018 ; Vigne et al, 2019 ). In the context of neutrophils, we found that the CD31 agonist consistently sustained CD31 phosphorylation ( Figure 4—figure supplement 1A ) and clustering ( Figure 4—figure supplement 1B ) during fMLP activation ( Figure 4—figure supplement 1C ), specifically targeting the CD31 molecule ( Figure 4—figure supplement 1D ), and fine-tuning cytoskeleton dynamics ( Figure 4—figure supplement 1E ).…”
Section: Resultsmentioning
confidence: 99%
“…Decreases in barrier resistivity should be accompanied by reorganization of membrane-localized tight junction proteins that line the gaps between adjacent endothelial cells. Thus, membrane-localization of CLDN-5 was assessed by fluorescent readout of spatial colocalization with platelet endothelial cell adhesion molecule 1 (PECAM-1), which is constitutively expressed along the membrane of vascular cells. , Loss of BBB integrity can manifest as a redistribution of membrane-localized CLDN-5 to increased intracellular clusters that no longer co-localize with PECAM-1 (Figure a,c). We also observed marked increases in the fluorescent readout of vascular cell adhesion molecule 1 (VCAM-1) in the bEnd.3 monolayers (Figure a,d), which typically exhibits low basal expression of VCAM-1.…”
Section: Results and Discussionmentioning
confidence: 99%
“…This observed change in TJ localization leading to decreased TEER is also consistent with the data from our positive control treatment with a tight junction-disrupting peptide (TJDP) derived from the first extracellular loop of Claudin-1 (37). Membrane-associated CLDN-5 was defined as CLDN-5 fluorescence colocalizing with expression of platelet endothelial cell adhesion molecule 1 (PECAM-1), which is constitutively expressed in cells of the vascular compartment and regulates vascular integrity and immune cell trafficking (38, 39). Additionally, previous reports observed induction of a pro-inflammatory state in endothelial cultures exposed to soluble S (6).…”
Section: Resultsmentioning
confidence: 99%